Catechols as Sources of Hydrogen Atoms in Radical Deiodination and Related Reactions. (8th July 2016) - Povie, Guillaume; Ford, Leigh; Pozzi, Davide; Soulard, Valentin; Villa, Giorgio; Renaud, Philippe
Abstract: When used with trialkylboranes, catechol derivatives, which are low‐cost and low toxicity, are valuable hydrogen atom donors for radical chain reactions involving alkyl iodides and related radical precursors. The system 4‐ tert ‐butylcatechol/triethylborane has been used to reduce a series of secondary and tertiary iodides, a xanthate, and a thiohydroxamate ester. Catechol derivatives are right in the optimal kinetic window for synthetic applications, as demonstrated by highly efficient radical cyclizations. Cyclizations leading to the formation of quaternary centers can be performed in an all‐at‐once process (no slow addition of the hydrogen atom donor) at standard concentrations. The H‐donor properties of catechol derivatives can be fine‐tuned by changing their substitution pattern. In slow radical cyclization processes, an enhanced ratio of cyclized/uncyclized products was obtained by using 3‐methoxycatechol instead of 4‐ tert ‐butylcatechol.